Effect of micro/nano-SiO2 on mechanical, thermal, and electrical properties of silicone rubber, epoxy, and EPDM composites for outdoor electrical insulations - Khan, Hidayatullah; Amin, Muhammad; Ali, Muhammad; Iqbal, Muhammad; Yasin, Muhammad (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this paper the influence of micro-sized (3 mu m) and nano-sized (10 nm) silica (SiO2) on mechanical, thermal, and electrical properties of silicon rubber (SiR), epoxy, and ethylene propylene diene monomer (EPDM) composites is presented. The micro- and nano-sized SiO2 particle-filled SiR, epoxy, and EPDM composites were formulated with 20% microsilica and 5% nanosilica by weight respectively. Among these composites, SiR-SiO2 amalgamation was performed by mixing using an ultrasonication procedure. Epoxy-SiO2 was compounded in two steps, i.e. dispersion of fillers and mixing, whereas EPDM-SiO2 compounding was performed with a two roll mill technique. With the addition of micro/nano-SiO2, the composites showed enhanced tensile strength of similar to 2.7 MPa, improved hardness, and reduced elongation at break. Further incorporation of micro/nano-sized particles resulted in high thermal stability for SiRnano composites (SNCs) as compared to epoxy and EPDM composites. Compared to SiR and EPDM composites, epoxy-nano composites showed the highest value of dielectric strength, i.e. 38.8 kV/mm. Meanwhile, the volume and surface resistivity of SNCs were found higher as compared to other investigated samples. Promising properties of SiR nanocomposites among all the investigated samples suggest that their application is more suitable for utilization in outdoor electrical insulations.
Keywords: SiR; epoxy; EPDM; microcomposites; nanocomposites